MODEL PEMBELAJARAN UNTUK MENUMBUHKAN KARAKTER PEDULI LINGKUNGAN MATA PELAJARAN IPA - Novianti, Ratika (JPB - Jurnal Pendidikan Biologi, 2022)
The character of caring for the environment must be grown from an early age. Environmental damage which was previously considered a local problem within a country, has now penetrated and spilled over into a global issue. The emergence of environmental problems is mostly caused by human activities. This indicates that human concern for the environment in which they live is starting to fade. Therefore concern for the environment needs to be instilled from an early age. The character of caring for the environment must be taught in junior high schools, one of which is through science learning. The purpose of this study was to form the character of caring for the environment in junior high school students through the science material learning model. The method used in this research is qualitative. Data was collected through documentation and literature studies. Data were analyzed through data reduction, data display, and conclusion drawing/verification which were restated through discussion in descriptive form. The results of the literature study show that the formation of a caring character for the environment through science learning can be done by designing student-focused learning. Science learning provides opportunities for students to interact with the environment directly. Several learning models that can be used by teachers to shape the character of caring for the environment in students, such as Problem Based Learning (PBL), Project Based Learning (PjBL), Contextual Teaching and Learning (CTL), and Outdoor Learning methods. Teaching materials and learning media also play an important role in shaping the character of caring for the environment in students.